Pengaruh Profitabilitas, Ukuran Perusahaan, Aktivitas, Komite Audit, dan Likuiditas Terhadap Sustainability Report - Rosa Oktavia Sinaga; Ai Hendrani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Sustainability report was created as a way to show a company's responsibility for its environment This research was conducted with the aim of seeing how profitability, company size, activity, audit committee, and liquidity relate to sustainability reports This study is a type of causality study that aims to see the relationship between independent and bound variables, with research designs that utilize secondary data sources, namely financial statements and sustainability Report obtained from the www.idx.co.id and company's website In this research, 15 companies have been selected using the purposive sampling method with a total of 45 objects studied, namely primary consumer goods sector companies that published sustainability reports during the period 2020 – 2022. Multiple regression analysis used in this study. This study shows that company size has a significant impact on disclosure in sustainability report, while variables profitability, activity, audit committee, and liquidity do not impact disclosure in sustainability report. Keywords: Profitability, Company Size, Activities, Audit Committee, Liquidity, Sustainability Report